Hi Doctor Strange! Play it again, and discover the Metaverse - Perceptions of the Metaverse among gamers - Cruz, M.; Oliveira, A. (CISTI'2023 - 18th Iberian Conference on Information Systems and Technologies, 2023)
New, past, or, in development, are common attributes given to the Metaverse concept. Possibly it is all of that, but the most important is how we perceive it. Our lives are being influenced and transformed by technology which has a huge impact on our social, physical, and virtual representations. Regarding what many authors say about this concept we may question: how do real people represent the Metaverse? The main objective of this study is to analyze how Portuguese adults think and feel about this concept. To achieve this goal, two focus groups were conducted, with a total of 8 participants - Portuguese adults, all of them digital gamers. The results showed us expected and unexpected findings that probably rely on the (still in development) definition of what is and what will be the Metaverse. The results will offer us a deep understanding of which concepts can be more relevant for our research, as items and dimensions to be considered in a Ph.D. research in development.